(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This study describes the design of high speed FIR filter design with low complexity using various types of adders and multiplication methods. This work also explores the significance of prefix addition in path delay reduction and it’s accelerating performance in various DSP applications. The FIR filters consist of two core functional units such as adder and multiplier. In many existing FIR filter designs the system performances are accelerated using various multiplication methodologies and some optimization techniques. This paper briefly investigates the necessities of the parallel prefix adder in path delay reductions and the influence of multiplier less FIR design in overall system performance. And conclude the performance metrics and trade off measures between complexity and path delay optimization level of various types of Prefix adders and multipliers. This work focuses on both high speed accumulation and multiplication units for high performance FIR filter design and its performance is compared with the existing FIR filter design in terms of delay and hardware utilization rate.